Pengaruh Electronic Banking Terhadap Kinerja Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2021 - Ginting, Mitha Christina; Sagala, Lamria Sagala; Panjaitan, Rike Yolanda; Situmorang, Duma Rahel (JURNAL MUTIARA AKUNTANSI, 2022)
The purpose of this study is to examine the impact of e-banking (ATM and mobile banking) on ​​the performance of Indonesian Stock Exchange listed companies in the banking sector from 2019 to 2021. Today, the rapid development of information technology affects many aspects of life, including banking. One of the challenges for the domestic banking industry is protecting customers amid increasingly complex and dynamic requirements regarding both the services and products offered. Therefore, modern and mature information technology is required to support the service. Researchers brought up the topic as a study in line with the increasing number of transactions that people in Indonesia make via e-banking. This shows an increasing trend every year. Although the survey is associative, the survey population is IDX-listed banking companies for the period 2019-2021. Sampling is performed using a targeted sampling technique. The sample used in this study included 38 banks with 3 years of follow-up. Data analysis was performed using a statistical application, namely multiple linear regression using SPSS. Tests have shown that ATMs have a positive impact on bank performance, as ATM distribution is currently distributed in different locations and they are easy to use. This has created a general perception that ATMs are ubiquitous and can transact indefinitely, and customer growth has an impact on financial performance. Second, M-banking affects the bank's financial performance. Many banks have adopted the use of M-banking because it is driven by the level of investment. In addition, the use of M-banking in general, many customers immediately take advantage of the possibilities of their mobile banking.